2013
DOI: 10.1088/1742-6596/417/1/012038
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Copper Nanoparticles in Liquid by Matrix Sputtering Process

Abstract: As a new method for nanoparticles preparation, magnetron sputtering of metal atoms and clusters into organic liquids has been intensively used recently. In this study, metallic copper nanoparticles dispersed in pentaerythritol ethoxylate were prepared by this process. Their size control was achieved by controlling the sputtering current. Specific absorption at ca. 580 nm was detected by UV-Vis measurement which is attributed to the specific plasmon absorption of metallic copper. TEM observation also revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 23 publications
3
30
0
Order By: Relevance
“…The anion and cation effect and the stabilization capability of ionic liquid for NPs have been also investigated and discussed elsewhere [55][56][57]. On the other hand, liquid monomers, which can be polymerized in the succeeding step, or liquid polymers were then used as a capture medium in sputtering [58][59][60][61][62][63]. This resulted in a composite of NPs embedded in a polymer matrix, which functions as a solid material [58,59,62].…”
Section: Brief History and Background Of Sputtering Onto A Liquidmentioning
confidence: 99%
“…The anion and cation effect and the stabilization capability of ionic liquid for NPs have been also investigated and discussed elsewhere [55][56][57]. On the other hand, liquid monomers, which can be polymerized in the succeeding step, or liquid polymers were then used as a capture medium in sputtering [58][59][60][61][62][63]. This resulted in a composite of NPs embedded in a polymer matrix, which functions as a solid material [58,59,62].…”
Section: Brief History and Background Of Sputtering Onto A Liquidmentioning
confidence: 99%
“…On the other hand, physical processes [17][18][19][20][21][22][23][24][25][26][27] (cluster beam deposition, 17 sputtering [18][19][20][21][22][23][24][25][26][27] ) that do not need reducing agents, have been used to produce metal nanoclusters from the bulk metal source. The great advantage of these techniques over chemical reduction methods is the high purity of the nanoclusters that can be achieved, as the synthesis is done under vacuum conditions using a controlled atmosphere.…”
mentioning
confidence: 99%
“…Recent progress in sputtering has shown that introducing a liquid substrate to replace the solid ones allowed for direct preparation of liquid dispersion of nanoclusters. [20][21][22][23][24][25][26] The liquid substrates are based on molten salts and low vapour pressure liquids such as liquid polymer, [22][23][24][25][26] vegetable oil, 30 and ionic liquids. 20,21,27 Moreover, when stabilizing molecules are added into the liquid substrate or sputtering atmosphere, it is possible to control particle size and properties (oxidation, surface functionalization, plasmonic/ uorescent properties).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, metal sputtering over liquid matrix 18 19 20 21 22 23 24 25 26 has been demonstrated in order to prepare colloidal metal NPs without the use of reductants. Moreover, we have developed this approach for organic–protected metal NPs, and termed it as the “matrix sputtering method” 18 19 20 21 22 23 . In a sputtering process, argon or nitrogen is ionized by a high voltage, which then attacks the target metal.…”
mentioning
confidence: 99%